(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to know the effect of using the method of questioning on the achievement of the third grade students in the Institute for the Preparation of Female Teachers in the subject of the Holy Quran.The limits of the current research included a sample of third-grade female students at the Teachers Preparation Institute / Al-Bayaa Al-Sabahi in the second semester of the academic year 2013-2014. The subject of the study was a number of texts from Surat Al-Baqara on what is included in the prescribed curriculum.In the second chapter, the researcher dealt with a theoretical framework entitled The Question in the Holy Qur’an, in which she talked about the Qur’an asking questions and the intent behind that, and how it proves faith truths and strengthens their consolidation in the hearts of people. connection.